1985
DOI: 10.1159/000242157
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine and Carnitine Transferases in the Intestinal Mucosa of Suckling Rats

Abstract: Carnitine acetyltransferase and palmitoyltransferase activity in the mucosa of the small intestine of rats rises after birth and falls at the time of weaning. The carnitine contents of the mucosa (free, acetyl-, palmitoyl- and total) decrease postna tally, reaching adult levels at the time of weaning. Orally administered 14C-carnitine is only slowly absorbed so that radioactivity is still high in plasma and organs 6 h later, whereas label given subcutaneously disappears from the plasma and tissues m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…Perhaps less fat is oxidized after weaning than before weaning, as is the general rule for other tis sues. The present data are also consistent with our previous findings that the mucosa of suckling rats produces ketones and that this production depends on the presence of carnitine [Hl-In the present study no attempt was made to define the mechanism of carnitine absorp tion in the rat small intestine although it has been reported that an active transport is involved [3][4][5], However, we [10] and others [3,5] have shown previously that the rate of carnitine absorption from the intestinal lu men is remarkably slow compared to the transport of other compounds. It has been suggested that this may be related in some way to the formation of carnitine esters in the intestinal mucosa [3], Finally it should be stressed that the everted small intestinal sac is an artificial preparation and results obtained with it need not reflect the in vivo situation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Perhaps less fat is oxidized after weaning than before weaning, as is the general rule for other tis sues. The present data are also consistent with our previous findings that the mucosa of suckling rats produces ketones and that this production depends on the presence of carnitine [Hl-In the present study no attempt was made to define the mechanism of carnitine absorp tion in the rat small intestine although it has been reported that an active transport is involved [3][4][5], However, we [10] and others [3,5] have shown previously that the rate of carnitine absorption from the intestinal lu men is remarkably slow compared to the transport of other compounds. It has been suggested that this may be related in some way to the formation of carnitine esters in the intestinal mucosa [3], Finally it should be stressed that the everted small intestinal sac is an artificial preparation and results obtained with it need not reflect the in vivo situation.…”
Section: Discussionsupporting
confidence: 93%
“…The endogenous release of carnitine was highest in the suckling rats and lowest in the older animals. This may be an actual reflection of the high endogenous car nitine content in the intestinal mucosa very early in life [10] but may also reflect the greater sensitivity of the infant gut to me chanical manipulations. In contrast, the transfer of carnitine from the mucosal to the The results are expressed as the amount of carnitine present in the serosal compartment following incuba tion of the everted sac in a mucosal solution free of carnitine (pmol/60 min/g wet intestine).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect Hahn and Taller [14] and Bekesi and Williamson [15] showed that the intestinal mucosa of neonatal rats has an increased capacity for ketogenesis. This process is accompanied by the increase in CPT I [16,17] and HMG-CoA synthase activities [15]. Mucosa of the rat small intestine has the intestinal expression of CPT I, since mRNA levels at birth are low but increase after the first lactation.…”
Section: Introductionmentioning
confidence: 99%
“…CPT activity that rises after birth, reaches a peak in the middle of the suckling period and falls at weaning [16].…”
Section: Introductionmentioning
confidence: 99%
“…The activity of a key enzyme, carnitine acyltransferase (ED 2.3.1.21), tends to peak during suckling [13,14], but remains relatively high in both the proximal and distal portions of the adult intestinal mucosa [13]. This finding of high activity in the distal intestine of suckling rats [13] lends further support to the importance of the HMG-CoA pathway for mucosal ketogenesis because HMG-CoA synthase is ab sent from the distal part of the intestine and ketogenesis is low. The rate of removal of [l-14C]palmitoyl-CoA by mitochondria from the intestines of suckling and adult rats is similar, but the production of l4C02 is 3-fold higher in the adult [14].…”
Section: Discussionmentioning
confidence: 99%